Dynamic Geometry: P78

Geometry Level pending

The diagram shows a unit black square. A red quarter circle is drawn using the side of the square as the radius. Two yellow semicircles are drawn. Each center moves on one square's side so the semicircles are growing, shrinking and are tangent to each other at any moment. Then, we draw a cyan circle so it's tangent to the two yellow semicircles and internally tangent to the red quarter circle. Finally we inscribed a blue circle between the cyan circle and the two yellow semicircles. When the sum of all radii (except the red quadrant) is equal to 117 112 \dfrac{117}{112} , the ratio of the larger semicircle's radius to the radius of the smaller semicircle can be expressed as p q \dfrac{p}{q} , where p p and q q are coprime positive integers. Find p + q p+q .


The answer is 97.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Preliminaries Let A B C D ABCD be the square. Denote the centers of the semicircles by K K , L L , their radii by r 1 {{r}_{1}} , r 2 {{r}_{2}} respectively. Denote by r 3 {{r}_{3}} , r 4 {{r}_{4}} the radii of the cyan and the blue circles respectively. Denote by E E the intersection of the perpendicular bisectors of A B AB and A D AD . Denote by Q Q , H H , R R and I I the intersections of these lines with the semicircles and sides B C BC and C D CD , as seen in the figure. Let J J be the intersection of line A E AE with the red arc.

Step 1: To prove that E E is the center of the cyan circle.
It is easy to see that Q Q and R R belong to the diagonal B D BD of the square. Moreover, Q E = K H K Q E H = K H K Q L B = 1 r 1 r 2 ( 1 ) QE=KH-KQ-EH=KH-KQ-LB=1-{{r}_{1}}-{{r}_{2}} \ \ \ \ \ (1) Similarly, E R = I L I E R L = I L D K R L = 1 r 1 r 2 ER=IL-IE-RL=IL-DK-RL=1-{{r}_{1}}-{{r}_{2}} Hence the circle with center E E and radius y = Q E = E R = 1 r 1 r 2 y=QE=ER=1-{{r}_{1}}-{{r}_{2}} is tangent to both semicircles. Furthermore, E J = A J A E = A J K L = 1 ( r 1 + r 2 ) = y EJ=AJ-AE=AJ-KL=1-\left( {{r}_{1}}+{{r}_{2}} \right)=y Thus, E E is the center of the cyan circle tangent to the semicircles and the red arc.

Step 2: To establish relations for r 1 {{r}_{1}} , r 2 {{r}_{2}} and r 3 {{r}_{3}}
From ( 1 ) (1) we get r 1 + r 2 + r 3 = 1 ( 2 ) {{r}_{1}}+{{r}_{2}}+{{r}_{3}}=1 \ \ \ \ \ (2) By Pythagorean theorem on A K L \triangle AKL we have

K L 2 = A K 2 + A L 2 ( r 1 + r 2 ) 2 = ( 1 r 1 ) 2 + ( 1 r 2 ) 2 K{{L}^{2}}=A{{K}^{2}}+A{{L}^{2}} \Rightarrow {{\left( {{r}_{1}}+{{r}_{2}} \right)}^{2}}={{\left( 1-{{r}_{1}} \right)}^{2}}+{{\left( 1-{{r}_{2}} \right)}^{2}} which gives r 1 + r 2 = 1 r 1 r 2 ( 3 ) {{r}_{1}}+{{r}_{2}}=1-{{r}_{1}}{{r}_{2}} \ \ \ \ \ (3) The latter, combined with ( 2 ) (2) gives r 1 r 2 = r 3 ( 4 ) {{r}_{1}}{{r}_{2}}={{r}_{3}} \ \ \ \ \ (4)

Step 3: To express r 4 {{r}_{4}} in terms of r 3 {{r}_{3}}
By Descartes’ Circle Theorem ,

k 4 = k 1 + k 2 + k 3 + k 4 + 2 k 1 k 2 + k 2 k 3 + k 3 k 1 1 r 4 = 1 r 1 + 1 r 2 + 1 r 3 + 2 1 r 1 1 r 2 + 1 r 2 1 r 3 + 1 r 3 1 r 1 1 r 4 = r 1 r 2 + r 2 r 3 + r 3 r 1 r 1 r 2 r 3 + 2 r 1 + r 2 + r 3 r 1 r 2 r 3 ( 2 ) , ( 4 ) 1 r 4 = r 3 + ( 1 r 3 ) r 3 r 3 2 + 2 1 r 3 2 1 r 4 = 4 r 3 r 3 r 4 = r 3 4 r 3 ( 5 ) \begin{aligned} {{k}_{4}}={{k}_{1}}+{{k}_{2}}+{{k}_{3}}+{{k}_{4}}+2\sqrt{{{k}_{1}}{{k}_{2}}+{{k}_{2}}{{k}_{3}}+{{k}_{3}}{{k}_{1}}} & \Rightarrow \frac{1}{{{r}_{4}}}=\frac{1}{{{r}_{1}}}+\frac{1}{{{r}_{2}}}+\frac{1}{{{r}_{3}}}+2\sqrt{\frac{1}{{{r}_{1}}}\cdot \frac{1}{{{r}_{2}}}+\frac{1}{{{r}_{2}}}\cdot \frac{1}{{{r}_{3}}}+\frac{1}{{{r}_{3}}}\cdot \frac{1}{{{r}_{1}}}} \\ & \Rightarrow \frac{1}{{{r}_{4}}}=\frac{{{r}_{1}}{{r}_{2}}+{{r}_{2}}{{r}_{3}}+{{r}_{3}}{{r}_{1}}}{{{r}_{1}}{{r}_{2}}{{r}_{3}}}+2\sqrt{\frac{{{r}_{1}}+{{r}_{2}}+{{r}_{3}}}{{{r}_{1}}{{r}_{2}}{{r}_{3}}}} \\ & \overset{\left( 2 \right),\left( 4 \right)}{\mathop{\Rightarrow }}\,\frac{1}{{{r}_{4}}}=\frac{{{r}_{3}}+\left( 1-{{r}_{3}} \right){{r}_{3}}}{{{r}_{3}}^{2}}+2\sqrt{\frac{1}{{{r}_{3}}^{2}}} \\ & \Rightarrow \frac{1}{{{r}_{4}}}=\frac{4-{{r}_{3}}}{{{r}_{3}}} \\ & \Rightarrow {{r}_{4}}=\frac{{{r}_{3}}}{4-{{r}_{3}}} \ \ \ \ \ (5)\\ \end{aligned}

Step 4: To find r 1 {{r}_{1}} , r 2 {{r}_{2}} and hence their ratio
Since the sum of all the radii equals 117 112 \dfrac{117}{112} we have r 1 + r 2 + r 3 + r 4 = 117 112 ( 2 ) 1 + r 4 = 117 112 ( 5 ) 1 + r 3 4 r 3 = 117 112 r 3 = 20 117 ( 6 ) {{r}_{1}}+{{r}_{2}}+{{r}_{3}}+{{r}_{4}}=\frac{117}{112}\overset{\left( 2 \right)}{\mathop{\Rightarrow }}\,1+{{r}_{4}}=\frac{117}{112}\overset{\left( 5 \right)}{\mathop{\Rightarrow }}\,1+\frac{{{r}_{3}}}{4-{{r}_{3}}}=\frac{117}{112}\Leftrightarrow {{r}_{3}}=\dfrac{20}{117} \ \ \ \ \ (6) ( 2 ) r 1 + r 2 = 1 r 3 ( 6 ) r 1 + r 2 = 97 117 \left( 2 \right)\Rightarrow {{r}_{1}}+{{r}_{2}}=1-{{r}_{3}}\overset{\left( 6 \right)}{\mathop{\Rightarrow }}\,{{r}_{1}}+{{r}_{2}}=\frac{97}{117} ( 4 ) 3 ( 6 ) r 1 + r 2 = 20 117 {{\left( 4 \right)}_{3}}\overset{\left( 6 \right)}{\mathop{\Rightarrow }}\,{{r}_{1}}+{{r}_{2}}=\dfrac{20}{117}

Hence, r 1 {{r}_{1}} , r 2 {{r}_{2}} are the roots of the quadratic equation x 2 97 117 x + 20 117 = 0 {{x}^{2}}-\dfrac{97}{117}x+\dfrac{20}{117}=0 , i.e. r 1 = 4 9 a n d r 2 = 5 13 {{r}_{1}}=\dfrac{4}{9} \ \ \ and \ \ \ {{r}_{2}}=\dfrac{5}{13} or vice versa.

Finally, the ratio of the larger yellow semicircle’s radius to the smaller yellow semicircle’s radius is 4 9 5 13 = 52 45 \dfrac{\dfrac{4}{9}}{\dfrac{5}{13}}=\dfrac{52}{45} For the answer, p = 52 p=52 , q = 45 q=45 , thus, p + q = 97 p+q=\boxed{97} .

Well, that is very detailed indeed, thanks !

Valentin Duringer - 2 months, 3 weeks ago
Chew-Seong Cheong
Mar 17, 2021

Let the centers and radii of the left semicircle, right semicircle and cyan circle be A A , B B , and C C and r r , r 1 r_1 , and r 2 r_2 respectively and the bottom-left vertex of the unit square be D D . By Pythagorean theorem , we note that

A D 2 + B D 2 = A B 2 ( 1 r ) 2 + ( 1 r 1 ) 2 = ( r + r 1 ) 2 2 2 r 2 r 1 = 2 r r 1 1 r = r 1 + r r 1 r 1 = 1 r 1 + r \begin{aligned} AD^2 + BD^2 & = AB^2 \\ (1-r)^2 + (1-r_1)^2 & = (r+r_1)^2 \\ 2 - 2r - 2r_1 & = 2rr_1 \\ 1 - r & = r_1 + rr_1 \\ \implies r_1 & = \frac {1-r}{1+r} \end{aligned}

Also note that A C = B D r + r 2 = 1 r 1 r + r 1 + r 2 = 1 r 2 = 1 r r 1 = r ( 1 r ) 1 + r = r r 1 AC = BD \implies r+r_2 = 1 - r_1 \implies r + r_1+r_2 = 1 \implies r_2 = 1-r-r_1 = \dfrac {r(1-r)}{1+r} = rr_1 .

Let the radius of the blue circle be r 3 r_3 . Then by Descarte's theorem ,

1 r 3 = 1 r + 1 r 1 + 1 r 2 + 2 1 r r 1 + 1 r 1 r 2 + 1 r 2 r = r r 1 + r 1 r 2 + r 2 r r r 1 r 2 + 2 r + r 1 + r 2 + r r r 1 r 2 = r 2 ( 1 + r + r 1 r 2 2 + 2 1 r 2 2 = 1 + 1 r 2 r 2 + 2 r 2 = 4 r 2 r 2 r 3 = r 2 4 r 2 \begin{aligned} \frac 1{r_3} & = \frac 1r + \frac 1{r_1} + \frac 1{r_2} + 2 \sqrt{\frac 1{rr_1} + \frac 1{r_1r_2} + \frac 1{r_2r}} \\ & = \frac {rr_1 + r_1r_2+r_2r}{rr_1r_2} + 2 \sqrt{\frac {r+r_1+r_2+r}{rr_1r_2}} \\ & = \frac {r_2(1+r+r_1}{r_2^2} + 2 \sqrt{\frac 1{r_2^2}} \\ & = \frac {1+1-r_2}{r_2} + \frac 2{r_2} = \frac {4-r_2}{r_2} \\ \implies r_3 & = \frac {r_2}{4-r_2} \end{aligned}

When the sum of all radii is 117 112 \dfrac {117}{112} :

r + r 1 + r 2 + r 3 = 117 112 1 + r 2 4 r 2 = 117 112 4 4 r 2 = 117 112 r 2 = 20 117 r ( 1 r ) ( 1 + r ) = 20 117 117 r 2 97 r + 20 = 0 ( 13 r 5 ) ( 9 r 4 ) = 0 Since r and r 1 are interchangeable. r , r 1 = 5 13 , 4 9 \begin{aligned} \blue{r + r_1 + r_2} + r_3 & = \frac {117}{112} \\ \blue 1 + \frac {r_2}{4-r_2} & = \frac {117}{112} \\ \frac 4{4-r_2} & = \frac {117}{112} \\ \implies r_2 & = \frac {20}{117} \\ \frac {r(1-r)}{(1+r)} & = \frac {20}{117} \\ 117 r^2 - 97 r + 20 & = 0 \\ (13r - 5)(9r - 4) & = 0 & \small \blue{\text{Since }r \text{ and }r_1 \text{ are interchangeable.}} \\ r, r_1 & = \frac 5{13}, \frac 49 \end{aligned}

Then the ratio of larger radius to the other radius is 4 9 13 5 = 52 45 \dfrac 49 \cdot \dfrac {13}5 = \dfrac {52}{45} and p + q = 52 + 45 = 97 p+q = 52+45 = \boxed{97} .

Thank you for posting !

Valentin Duringer - 2 months, 3 weeks ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...